Are we ready for the challenge of banks 4.0? Designing a roadmap for banking systems in industry 4.0 - Amir Mehdiabadi; Mariyeh Tabatabeinasab; Cristi Spulbăr; Amir Karbassi Yazdi; Ramona Birau (International Journal of Financial Studies, 2020)
The purpose of the present paper is to provide an advanced overview of the practical applications of Banking 4.0 in Industry 4.0. This paper examines the technology trends in the Fourth Industrial Revolution and identifies the key indicators behind the creation of a strategic map for the fourth-generation banks and their readiness to enter Industry 4.0. This paper examines a systematic review of fully integrated Banking 4.0 and the application of the technologies of Industry 4.0 and illustrates a distinct pattern of integration of Banking 4.0 and Industry 4.0. One of the prominent features of this article is the performance of successful global banks in applying these technologies. The results showed that Banking 4.0 in Industry 4.0 is an integrative value creation system consisting of six design principles and 14 technology trends. The roadmap designed for banks to enter Industry 4.0 and how they work with industrial companies will be a key and important guide.
Keywords: 330; digitalization; banking 4.0; big data; industry 4.0; roadmap; technology